Régiók a Kárpát-medencében : múlt vagy jövő - Csüllög, Gábor (Közép-Európai Közlemények, 2008)
By social geographical analysis of the areal organization of the Hungarian historical statehood regional components and processes of the large area are identifiable. In the light of these components the Hungarian state does not appear as a loose conglomerate of provinces or as a simple structure organized rigidly around a central region. The process of regionalization, determinant in the construction of the country structure, was built on this regional operativity, with close interactions between theses two elements of regionalism. It is apparent that the larger regional units and the administratively defined counties are not substitutive or fungible areal forms, but complementing structural units interweaving and cohering larger areas.